Influence of Calcined Bauxite Aggregate on the Resistance of Cement Composites Subjected to Small Caliber Deformable Projectile Impact - Zhang, Fengling; Zhong, Rui (Frontiers in Materials, 2021)
This paper presents an experimental investigation on the influence of calcined bauxite aggregates (CBA) on the resistance of cement composites subjected to small caliber deformable projectile impact at a target velocity of 400 m/s. The deformable projectile was made from copper with a purity of 99.5% and a diameter of 8.0 mm. Compared to mixtures with conventional coarse granite aggregate and/or siliceous fine aggregate, the incorporation of either fine or coarse CBA or their combination is beneficial in reducing the depth of penetration (DOP), equivalent crater diameter (CD), and crater volume (CV) caused by deformable projectile impact. CBA is found to be more effective in controlling the DOP and CV in comparison to the CD. Replacing of conventional aggregate with CBA led to more severe damage to the projectiles (e.g. projectile length reduction, diameter increase, and mass loss). Relative effective hardness is an effective indicator to the deformation potential and penetration capacity of a deformable projectile to impact cement composites incorporating CBA.